'And I am re-begot': the textual afterlives of John Donne - Rundell, K (2016)
This thesis is a cultural history of the textual afterlives and poetic appropriations of John Donne's verse. I use print and manuscript miscellanies, hitherto unstudied commonplace books, letters, diaries and seventeenth and eighteenth century criticism to ask, who was reading Donne and in what physical forms? By looking at allusive strategies and reading practices of the time, I demonstrate how many different Donnes can be identified when we strip away modern notions of what 'Donne' is and seek multiple afterlives. I nuance the idea of Donne as a determinedly coterie poet, suggesting his print presence might have looked to his early audience like a strategic writer who had not, despite Izaak Walton's narrative, closed off the possibility of public authorship. I find there was a period of radical re-appropriation and re-reading of Donne in the seventeenth and eighteenth century: Donne was as a guiding influence to canonical poets. Rochester is perhaps the poet whose voice most vividly recalls Donne's swaggering persona and intricately-constructed rendering of apparent spontaneity. Katherine Philips's verse makes sophisticated use of Donne's voice in her intimate quasi-erotic verse; I contrast this with the voice of her poems written for state occasions to show how Donne becomes a resource for self-revelation. Dryden offers a sustained critical vision of Donne: although, as the primary mercenary proponent of mass popular literature, he may seem initially wholly unDonnean, I show how his verse both explicitly and obliquely negotiates with Donne's wit and form. I end by looking at the problematic offered by the negotiates with Donne's wit and form. I end by looking at the problematic offered by the dual critique and celebration in Pope's versification of Donne's Satyres, and at the Dunciad, to see where the limits of allusion come up against Pope's cacophonous multiplicity of voices. These four poets take different threads from Donne's canon to different ends and, in so doing, create different Donnes.